Effects of high temperature and drought on a hybrid bluegrass compared with Kentucky bluegrass and tall fescue - Su, Kemin; Bremer, Dale J.; Keeley, Steven J.; Fry, Jack D. (My University, 2009)
High temperature and drought stresses may reduce quality in cool-season turfgrasses during summer months in the transition zone. This growth chamber study was conducted to evaluate effects of high temperature and drought on physiology and growth of ‘Apollo’ Kentucky bluegrass (Poa pratensis L.) (KBG), ‘Dynasty’ tall fescue (Festuca arundincea Schreb.) (TF), and ‘Thermal Blue’, a hybrid (HBG) between KBG and Texas bluegrass (Poa arachnifera Torr.). Turfgrasses were exposed for 48 days to supra-optimal (high temperature; 35/25[degree]C, 14-h day/10-h night) and optimal (control; 22/15oC, 14-h day/10-h night) temperatures under well-watered (100% evapotranspiration [ET] replacement) and deficit (60% ET replacement) irrigation. Heat resistance was greater in HBG, which had greater visual quality, gross photosynthesis (P[subscript]g), dry matter production, and lower electrolyte leakage and soil-surface temperatures than KBG and TF under high temperature. Cumulative Pg during the study was 16% and 24% greater in HBG than in KBG and TF, respectively. Green leaf area index (LAI) in HBG was not affected by high temperature, but LAI was reduced by 29 % in KBG and 38% in TF. Differences in drought resistance were negligible among species. The combination of high temperature and drought caused rapid declines in visual quality and dry matter production, but HBG generally performed better. Results indicated greater heat resistance, but not drought resistance, in HBG than in KBG or TF.
Keywords: Warm season turfgrasses; Heat pulse technique; Soil water content; Creeping bentgrass; Evapotranspiration rates; Physciological responses